Clinical profile of dogs affected by distemper disease - Mariga, Carollina; Melazzo de Andrade, Cinthia; Krause, Alexandre; Tadeu Lemos Pinto Filho, Saulo (Pubvet, 2022)
This study aimed to classify the clinical profile of dogs affected by distemper disease at the Veterinary University Hospital of a higher education institution in Rio Grande do Sul. The clinical histories of the animals seen at the hospital from January 2017 to July 2019 were reviewed, using the patients’ medical records. During this period, 365 animals were suspected to have distemper disease. The prevalence of disease was 11,5% (42/365). Positive patients were classified according to breed, gender, age, and vaccination status, then separated according to the bodily systems involved: digestive, neuromuscular, multisystemic, hematopoietic, respiratory, lymphatic, ophthalmic, urinary and cutaneous; clinical signs and the presence of concomitant diseases. Distemper disease affects animals of mixed breed and younger than one year old more frequently, however, it has no predisposition for gender. The researchers observed that most dogs had no previous vaccination history. This study highlights the infection patterns of this viral disease, which mainly affects young unvaccinated animals, reinforcing the notion that preventive measures are essential for his control and the protection of the health of canine populations.
Keywords: Clinical signs; distemper disease; prevalence; systems